Perceived yoga exercise benefits and barriers of university students by gender: Results of a survey research - Roghaiyeh Kabiri; Syed Kamaruzaman Syed Ali; Zulnaidi Hutkemri (Turkish Journal of Kinesiology, 2018)
This study was conducted to explore perceived yoga exercise benefits and barriers of university students based on their gender. Participants (n=210) were university of Malaya undergraduate students from faculty of education in Kuala Lumpur. The method of sampling was cluster random sampling. This study utilized a quantitative methodology research to investigate the perceived benefits and barriers towards yoga exercise among university students using the health belief model. This was a survey study of data collection. One-way MANOVA was used to determine the differences. Some 197 subjects completed the questionnaire and the results of inferential analysis demonstrated that males and females are similar in reporting perceived benefits in the Psychological dimension F (1,195) = .55, sig = .46 (p > .05), Physical dimension F (1,195) =.05, sig=.835 (p > .05), Disease Prevention dimension F(1,195)=1.11, sig = .29(p > .05), Social dimension F(1,195) =.09, sig = .92 (p > .05). They are also similar in reporting perceived barriers in the Negative Preconception dimension F (1,195) = .20, sig=.66 (p>.05), Cost dimension F(1,195) = 2.36, sig. =.13(p >.05), Time Prevention dimension F(1,195) = .71, sig =.40 >.05 and Fears dimension F(1,195) =.71, sig = .40(p > .05). This study tried to determine how students' gender could influence their perceptions about yoga exercise. The results of this study show that males and female are similar in their perceived benefits and barriers to yoga exercise. Hence, in creating yoga exercise intervention for university students, gender is not a vital component to consider.